Green Rust: The Simple Organizing ‘Seed’ of All Life? - Michael J. Russell (Life, 2018)
Korenaga and coworkers presented evidence to suggest that the Earth’s mantle was dry and water filled the ocean to twice its present volume 4.3 billion years ago. Carbon dioxide was constantly exhaled during the mafic to ultramafic volcanic activity associated with magmatic plumes that produced the thick, dense, and relatively stable oceanic crust. In that setting, two distinct and major types of sub-marine hydrothermal vents were active: ~400 °C acidic springs, whose effluents bore vast quantities of iron into the ocean, and ~120 °C, highly alkaline, and reduced vents exhaling from the cooler, serpentinizing crust some distance from the heads of the plumes. When encountering the alkaline effluents, the iron from the plume head vents precipitated out, forming mounds likely surrounded by voluminous exhalative deposits similar to the banded iron formations known from the Archean. These mounds and the surrounding sediments, comprised micro or nano-crysts of the variable valence FeII/FeIII oxyhydroxide known as green rust. The precipitation of green rust, along with subsidiary iron sulfides and minor concentrations of nickel, cobalt, and molybdenum in the environment at the alkaline springs, may have established both the key bio-syntonic disequilibria and the means to properly make use of them—the elements needed to effect the essential inanimate-to-animate transitions that launched life. Specifically, in the submarine alkaline vent model for the emergence of life, it is first suggested that the redox-flexible green rust micro- and nano-crysts spontaneously precipitated to form barriers to the complete mixing of carbonic ocean and alkaline hydrothermal fluids. These barriers created and maintained steep ionic disequilibria. Second, the hydrous interlayers of green rust acted as engines that were powered by those ionic disequilibria and drove essential endergonic reactions. There, aided by sulfides and trace elements acting as catalytic promoters and electron transfer agents, nitrate could be reduced to ammonia and carbon dioxide to formate, while methane may have been oxidized to methyl and formyl groups. Acetate and higher carboxylic acids could then have been produced from these C1 molecules and aminated to amino acids, and thence oligomerized to offer peptide nests to phosphate and iron sulfides, and secreted to form primitive amyloid-bounded structures, leading conceivably to protocells.